Level of knowledge on preventive measures against intestinal parasitoses in parents, Portoviejo-Ecuador - Bracho Mora, Angela Maria; Mendoza Malavé, Gema Gabriela; Chancay Quimis, Karla Jahaira; Rivero de Rodríguez, Zulbey; Castro-Jalca, Jazmín; Castro-Jalca, Alexander (Kasmera, 2024)
Intestinal parasitosis are infections that can be caused by the ingestion of cysts (or oocysts) of protozoa, eggs, helminth larvae or by the penetration of larvae transcutaneous. One of the main bases to prevent them is the fulfillment of basic hygienic measures. The purpose of this research is to determine the level of knowledge about preventive measures for intestinal parasitosis among parents of the Municipal School of Portoviejo, Ecuador. An observational, descriptive, cross-sectional and prospective study was carried out, in which 217 families who wished to contribute to the study were evaluated and a survey was conducted. Most of the parents were found to be between 39 and 49 years of age, with a higher education level and a home occupation; as regards knowledge of preventive measures for intestinal parasitosis, most of the parents showed a "good" level of knowledge, according to the classification made here. It is concluded that the parents of the Ciudadela Municipal know about the norms of prevention against intestinal parasitosis, which should contribute to improve the quality of life of the population